The Impact of Radiation on the Tumor Microenvironment: Effect of Dose and Fractionation Schedules. (8th March 2018) - Arnold, Kimberly M; Flynn, Nicole J; Raben, Adam; Romak, Lindsay; Yu, Yan; Dicker, Adam P; Mourtada, Firas; Sims-Mourtada, Jennifer
In addition to inducing lethal DNA damage in tumor and stromal cells, radiation can alter the interactions of tumor cells with their microenvironment. Recent technological advances in planning and delivery of external beam radiotherapy have allowed delivery of larger doses per fraction (hypofractionation) while minimizing dose to normal tissues with higher precision. The effects of radiation on the tumor microenvironment vary with dose and fractionation schedule. In this review, we summarize the effects of conventional and hypofractionated radiation regimens on the immune system and tumor stroma. We discuss how these interactions may provide therapeutic benefit in combination with targeted therapies. Understanding the differential effects of radiation dose and fractionation can have implications for choice of combination therapies.